Collision risk measure for triggering evasive actions of maritime autonomous surface ships. (July 2020) - Huang, Yamin; van Gelder, P.H.A.J.M.
Highlights: Incorporating ship dynamics and various constraints in collision risk assessment. Applying bow-tie theory to assess real-time collision risk for ship navigation. Offering a new perspective of risk measurement for supporting timely evasive action. Demonstrating the failure mode of existing risk measurements. Abstract: Collision risk assessment is essential for supporting collision avoidance, which is the core of various collision alert/avoidance systems. One main task of the systems is setting off alarms for taking evasive actions. The alarms need to be triggered before the conflict has no collision-free solution. However, most of existing collision risk measures are independent of conflict resolution. That means the collision alert does not indicate that the collision is avoidable or not. This article proposes an improved time-varying collision risk (TCR) measure, bringing in a new measure. The measurement of TCR reflects not only the dangerous level of the approaching ships but also the difficulty of avoiding collisions. By comparing with traditional measures, e.g., Collision Risk Index (CRI), we found that (1) the TCR can distinguish changes of risk that have identical CRI level, (2) the TCR measure offers a reasonable tool to evaluate the collision risk of entire traffic, and (3) it reflects the influence of maneuverability improvement on collision risk. Based on those results, this article reaches two conclusions: the collision risk is monotonically increasing when introducing more ships, and ignorance of ship maneuverability results in an underestimation of collision risk.